Curcuma zedoaria (Christm.) Roscoe: Benefits and Bioactivity - Marina Silalahi (HM Publisher, 2020)
Curcuma zedoaria (Christm.) Roscoe or Temu Putih is a native plant in India and has been long cultivated in Indonesia. By the local communities in Java, it has been used as a component of the Jammu and the traditional medicine. This article is based on literature from offline and online media. Offline literature used the books, whereas online media used Web, Scopus, Pubmed, and scientific journals. Based on a study of ethnobotany Curcuma zedoaria was used as medicine and spices. The main secondary metabolites of Curcuma zedoaria rhizomes are terpenoids, especially sesquiterpenoids and monoterpenoids. Curcuma zedoaria have bioactivities as anticholesterol, anti-tumor/cancer, anti-inflammation, fever, antipyretic, analgesic dan anti-microbial